2017
DOI: 10.3390/rs9080778
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Use of Remote Sensing and Modeling to Assess an Anomalously High Chlorophyll-a Event during Summer 2015 in the South Central Red Sea

Abstract: An anomalously high chlorophyll-a (Chl-a) event (>2 mg/m 3 ) during June 2015 in the South Central Red Sea (17.5 • to 22 • N, 37 • to 42 • E) was observed using Moderate Resolution Imaging Spectroradiometer (MODIS) data from the Terra and Aqua satellite platforms. This differs from the low Chl-a values (<0.5 mg/m 3 ) usually encountered over the same region during summertime. To assess this anomaly and possible causes, we used a wide range of oceanographical and meteorological datasets, including Chl-a concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 72 publications
8
39
0
Order By: Relevance
“…Notably, a lag correlation analysis revealed a statistically significant two-month positive lag correlation between dust anomalies and Chl-a anomalies using the MODIS-Aqua dataset. A similarly significant two-month negative lag correlation was identified between SST anomalies and Chl-a anomalies [199].…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…Notably, a lag correlation analysis revealed a statistically significant two-month positive lag correlation between dust anomalies and Chl-a anomalies using the MODIS-Aqua dataset. A similarly significant two-month negative lag correlation was identified between SST anomalies and Chl-a anomalies [199].…”
Section: Introductionsupporting
confidence: 52%
“…Using the MODIS-Aqua Chl-a product, Li et al [199] revealed a two-month lag correlation positive dust anomalies and high Chl-a anomalies, as well as a two-month lag correlation between negative SST anomalies and high Chl-a anomalies. In this work, we use the OC-CCI dataset to further test and validate the results obtained from [199].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations